Three new Brazilian species of the sharpshooter genus Geitogonalia Young (Hemiptera: Cicadellidae: Cicadellini) - Cavichioli, Rodney R.; Rendón-Mera, Diana I.; Domahovski, Alexandre C.; Mejdalani, Gabriel (Zootaxa, 2018)
Three new Brazilian sharpshooter species of the genus Geitogonalia Young, 1977 are described: G. buccina sp. nov., G. piei sp. nov., and G. tetracorni sp. nov. The first species is known from the states of Rio de Janeiro and Minas Gerais, whereas the second and third species are from the state of Paraná. We provide descriptions of the male and female (except for G. piei), photographs and illustrations, as well as a revised diagnosis of the genus and a key to the five known species.